Palm OS Programming Bible - Foster, Lonnon R. (IDG Books Worldwide, 2011)
With complete coverage of the new Palm wireless and Web capabilities, this one-step reference shows programmers how to create next-generation applications for Palm OS devices using all the latest development platforms and tools. The author has tested the many code samples against all Palm OS versions right up to the new OS 3.5. The value-packed CD-ROM includes development tools, demos, and sample code.